Using text and voice chat modes to enhance students' performance in discourse functions. (2015) - Jasim, Watheq Hameed; AbuSeileek, Ali Farhan
This study aimed to explore the effect of using text and voice chat modes on undergraduate EFL students' performance in discourse functions in English. Fifty-one undergraduate male and female students were selected as the study sample. They were randomly assigned into three groups, two experimental (CMC text chat and voice chat) and one control group (regular instruction). A pre-post test to measure students' performance in discourse functions was administered to all students who participated in the study. The findings of the study showed that there were statistically significant differences between the mean scores of the experimental (CMC chat) groups and the control group (regular instruction) in favour of the experimental groups. Furthermore, the findings revealed that both of the text and voice chat groups improved discourse functions in the same way. The findings revealed that there were no significant differences between the mean scores due to technique (text chat and voice chat). The results also revealed there was no statistically significant correlation between chat modes and experimental group students' performance on the discourse functions.